Handling and garment construction techniques using Inabel fabric - Peralta, Angel Dei R.; Rayala, Maria Monica E. (Quezon City College of Home Economics, University of the Philippines Diliman, 2016)
Inabel, a well-known hand-woven fabric from the Ilocos region is mostly used in blankets, bags, furniture and home decor. Today, inabel is also being used on garments for both formal wear and ready-to-wear. The researcher had a personal encounter with designers that use inabel and they mentioned that there are difficulties in constructing garments using inabel because of its fragility. This experimental study aimed to determine effective and appropriate handling and garment construction techniques used for inabel fabric that could address existing problems experienced by selected designers. The researcher interviewed five local designers who were purposively selected for their experience in using inabel fabric specifically from Paoay, Ilocos Norte. The researcher was able to determine the two main problems that the designers encounter when using inabel fabric: excessive fraying and seam slippage. To establish the best needle size and stitch per inch (SPI) in sewing inabel, several tests were performed. It was determined that the most appropriate needle size is 11/75 and 14/90 and the best SPI is 22. The researcher came up with (1) Seam Type Experiment to address the seam slippage and (2) the Gelatin Stabilizer Experiment to address the fraying of the fabric. As a result, the researcher was able to determine that French seam is the most appropriate seam type to prevent seam slippage. Based on the gelatin experiment, it was found that gelatin can lessen the fraying of inabel fabric and may be useful in handing inabel during construction of garments. The researcher recommends further experiments on other handling and garment construction techniques that can address the fraying and seam slippage of inabel and also further experiment on other forms of stabilizers to determine other handling techniques in using inabel.
Thesis (BS Clothing Technology)--University of the Philippines Diliman, June 2016.
Keywords: Textile fabrics -- Philippines -- Ilocos region; Garment cutting -- Philippines